IDENTIFIKASI DAN PREVALENSI EKTOPARASIT IKAN NILA (OREOCHROMIS NILOTICUS) DI PULAU LOMBOK - LUH GEDE SUMAHIRADEWI; INDAH SORAYA; NOVITA TRI ARTININGRUM; TARISKA ARDIA NINGSIH (GANEC SWARA, 2023)
This study aims to determine the type of ectoparasites and the level of prevalence and intensity with which they attack tilapia. The method used in this study is a survey method with a purposive sampling technique. Sampling was carried out at five locations on the island of Lombok, namely West Lombok, Central Lombok, East Lombok, North Lombok, and Mataram City. At each location, four fish were taken and examined at the Parasite Laboratory of the Fish Quarantine Center for Quality Control and Safety of Fishery Products in Mataram. Observation of ectoparasites was carried out on the outside of the tilapia, namely mucus, gills, and fins. Parameters observed in this study included identification of the type of ectoparasites that attacked, prevalence and intensity of ectoparasites in tilapia, and water quality as supporting data. The research data obtained was analyzed descriptively. The results showed that there were 3 types of ectoparasites identified, namely Tricodina sp., Dactylogirus sp., and Gyrodactylus sp. The highest prevalence rate of Trichodina sp. and Gyrodactylus sp. is located in Mataran with values of 100 and 75%, while the highest prevalence rate of Dactylogyrus sp. is in North Lombok with 100%. The highest intensity of Trichodina sp. was in the city of Mataram in the moderate category; Gyrodactylus sp. was highest in the low category of West Lombok; and Dactylogyrus sp. was in the medium category in North Lombok